The Effectiveness of STAD Model Assisted with Animation Film in the Learning of Writing Folklore of Grade IV Students - Hastuti, Hastuti; Mardikantoro, Hari Bakti; Isnaeni, Wiwi (Journal of Primary Education, 2019)
The purpose of this study was to determine the difference between the effectiveness of folklore writing learning taught by using the STAD model assisted with animated films and conventional learning. This study applied a quantitative research method with the research type of Quasy Experimental Design. The quasi-experimental design used in this study was pre-test – post-test Nonequivalent control group design. The sample of this study was SD N 207 Dampang as the experimental class and SDN 232 Dampang as the control class. Data collection technique was done by using test and non-test techniques. The results showed that there was a significant difference in the average score of learning folklore writing between the control class and the experimental class with a significance level of 0.05 and the N-gain value of the experimental class 0.37 in the medium category and that of the control class is 0.26 in the low category.